Eating attitudes among adolescent girls in Tehran: A schoolbased survey between 2010-2011 - Sanaei, Hasti; Dabiran, Soheila; Seddigh, Leila (Social Determinants of Health, 2016)
Background: Eating attitude disorders may indicate an increased risk for eating disorders and their chronic health complications. The purpose of the present study was to determine the prevalence of eating attitude disorders and to identify the factors associated with them among female students in Tehran. Methods: A total of 14–18 year-old high school girls (N=619) completed a standardized selfreport Eating Attitude Test (EAT-26) questionnaire and a demographic questionnaire. Mental health problems were investigated by means of the Patient Health Questionnaire-2 and the Generalized Anxiety Disorders-2. Results: Based on EAT-26 scores, 153 (24.7%) students had eating attitude disorders. There was no relationship between abnormal eating attitudes and both individual and socioeconomic factors (P>0.05). Logistic regression analysis demonstrated that eating attitude disorders were significantly associated with depression [OR=1.8 (1.2-2.8), P=0.007], anxiety [OR=1.6 (1.1- 2.4), P=0.04], and perception of body shape as overweight [OR=2.7 (1.7-4.3), P<0.001]. Conclusion: A relatively high rate of eating attitude disorders was found among adolescent school girls in Tehran. Related factors were body image and psychological issues including depression and anxiety. Preventive and screening programs in schools could identify students at risk and prevent development and complications of eating disorders.